2014
DOI: 10.1002/ejhf.164
|View full text |Cite
|
Sign up to set email alerts
|

Adding the acetylcholinesterase inhibitor, donepezil, to losartan treatment markedly improves long‐term survival in rats with chronic heart failure

Abstract: AimsModulation of vagal tone using electrical vagal nerve stimulation or pharmacological acetylcholinesterase inhibition by donepezil exerts beneficial effects in an animal model of chronic heart failure (CHF). Considering different treatment mechanisms underlying renin-angiotensin system (RAS) suppression and parasympathetic activation, we hypothesized that parasympathetic activation together with RAS inhibition could attenuate CHF progression. To test this hypothesis, we investigated the therapeutic effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…129,130 However, the mortality rate of heart failure patients remains high. 39 In that study, donepezil was added to losartan (ARB) and this combination decreased neurohumoral activation and adverse cardiac remodelling, improved cardiac function and increased survival in rats with heart failure compared to losartan alone. 39 In that study, donepezil was added to losartan (ARB) and this combination decreased neurohumoral activation and adverse cardiac remodelling, improved cardiac function and increased survival in rats with heart failure compared to losartan alone.…”
Section: Inhibitors Combined With Other Interventions In Heart Failurmentioning
confidence: 99%
See 2 more Smart Citations
“…129,130 However, the mortality rate of heart failure patients remains high. 39 In that study, donepezil was added to losartan (ARB) and this combination decreased neurohumoral activation and adverse cardiac remodelling, improved cardiac function and increased survival in rats with heart failure compared to losartan alone. 39 In that study, donepezil was added to losartan (ARB) and this combination decreased neurohumoral activation and adverse cardiac remodelling, improved cardiac function and increased survival in rats with heart failure compared to losartan alone.…”
Section: Inhibitors Combined With Other Interventions In Heart Failurmentioning
confidence: 99%
“…131 Novel therapeutic strategies involved in both RAS suppression and parasympathetic activation were demonstrated by Li and coworkers. 39 In addition, several reports demonstrated that exercise training to modulate vagal activity could provide greater efficacy when added to treatment with an AChE inhibitor as shown in experimental studies of heart failure. These findings suggested that AChE inhibitors may provide effects synergistic with conventional treatment in cases of heart failure to improve the outcome.…”
Section: Inhibitors Combined With Other Interventions In Heart Failurmentioning
confidence: 99%
See 1 more Smart Citation
“…17 None of the studies involving pro-cholinergic agents in the treatment of heart failure have reached clinical application yet. [18][19][20][21][22] Pyridostigmine is a reversible acetylcholine esterase inhibitor, it augments the effect of the parasympathetic system. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] It is currently used in the treatment of myasthenia gravis.…”
Section: Pyridostigminementioning
confidence: 99%
“…We read with great interest the study by Li et al who demonstrated that the addition of donepezil prevented the deterioration of heart dysfunction and improved the longterm survival in rats with chronic heart failure (CHF) beyond that seen with losartan alone. 1 This suggested that combination treatment with losartan plus donepezil might be a potential therapeutic strategy for CHF.…”
Section: Donepezil a Potential Therapeutic Agent For Heart Failurementioning
confidence: 99%